EVOLUTION OF INNER CRUSTAL DISPLACEMENT DEFICIT ACCORDING TO THE GPS DATA IN CONNECTION WITH SEISMICITY IN THE PERIOD OF 2014–2024 AND THE MW=7.4 HUALIEN EARTHQUAKE, TAIWAN - V. I. Kaftan; A. Yu. Melnikov; P. A. Dokukin (Геодинамика и тектонофизика)
The study deals with the analysis of the evolution of seismicity and inner crustal movements in Taiwan over the past 10 years. The primary data sources included time series generated from permanent GPS observations, the earthquake catalog, and the location of the main tectonic structures. Horizontal displacement vectors of GPS stations were determined for each day, relative to the initial epoch. An inner reference system was used in the absence of general area motion defined in the global coordinate system. An animation video was made for synoptic analysis of the evolution of internally generated seismic and tectonic motions. It is shown that the majority of strong M≥6 earthquakes occurred within the boundaries of the inner crustal movement deficit zones or thereon. This allows us to consider such highstrength crustal areas as prognostic signs of earthquakes. They are revealed by GPS observations over several years and destroyed by strong seismic events, as well as by large groups of moderate and weak earthquakes. By 2024, on the island there was formed an east-to-west elongated high-strength zone. It connects the place of convergence of the Ryukyu and Manila trenches with the insular land. It can be assumed that this area marks a zone of high seismic-generating stresses, which is important to take into account in further assessment of seismic hazard.